High incidence of large deletions in the PMS2 gene in Spanish Lynch syndrome families. (28th July 2013) - Brea‐Fernández, A.J.; Cameselle‐Teijeiro, J.M.; Alenda, C.; Fernández‐Rozadilla, C.; Cubiella, J.; Clofent, J.; Reñé, J.M.; Anido, U.; Milá, M.; Balaguer, F.; Castells, A.; Castellvi‐Bel, S.; et al.
<x xml:space="preserve">Abstract</x> Lynch syndrome (LS) is caused by germline mutations in one of the four mismatch repair (MMR) genes. Defects in this pathway lead to microsatellite instability (MSI) in DNA tumors, which constitutes the molecular hallmark of this disease. Selection of patients for genetic testing in LS is usually based on fulfillment of diagnostic clinical criteria (i.e. Amsterdam criteria or the revised Bethesda guidelines). However, following these criteria PMS2 mutations have probably been underestimated as their penetrances appear to be lower than those of the other MMR genes. The use of universal MMR study‐based strategies, using MSI testing and immunohistochemical (IHC) staining, is being one proposed alternative. Besides, germline mutation detection in PMS2 is complicated by the presence of highly homologous pseudogenes. Nevertheless, specific amplification of PMS2 by long‐range polymerase chain reaction (PCR) and the improvement of the analysis of large deletions/duplications by multiplex ligation‐dependent probe amplification (MLPA) overcome this difficulty. By using both approaches, we analyzed 19 PMS2‐suspected carriers who have been selected by clinical or universal strategies and found five large deletions and one frameshift mutation in PMS2 in six patients (31%). Owing to the high incidence of large deletions found in our cohort, we recommend MLPA analysis as the first‐line method for searching germline mutations in PMS2.